2012
DOI: 10.1074/jbc.m112.386599
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β/SMAD Target Gene SKIL Is Negatively Regulated by the Transcriptional Cofactor Complex SNON-SMAD4

Abstract: Background: Human SKIL gene encodes for SNON, a negative regulator of the TGF-␤/SMAD pathway. Results: We provide a molecular mechanism of transcriptional regulation of SKIL gene expression by TGF-␤/SMADs. Conclusion: Transcriptional cofactor complex SNON-SMAD4 negatively controls the expression of SKIL gene. Significance: The formation and function of complex SNON-SMAD4 are impaired in cancer cells lacking SMAD4, which affects TGF ␤-target gene regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 56 publications
2
33
1
Order By: Relevance
“…This regulation also suggests a time-dependent, negative feedback mechanism on TGF-␤ 1 signaling (58). This has been confirmed in a study by Tecalco-Cruz et al (64) who demonstrated a cluster of functional SBEs within the proximal promoter of the human SnoN gene, which were found to be conserved in the mouse (64). It is curious to note that the Ski gene does not appear to be a direct target of TGF-␤ 1 signaling, which suggests yet another level of complexity to the cellular control of the members of the Ski family of negative TGF-␤ 1 regulators.…”
supporting
confidence: 77%
“…This regulation also suggests a time-dependent, negative feedback mechanism on TGF-␤ 1 signaling (58). This has been confirmed in a study by Tecalco-Cruz et al (64) who demonstrated a cluster of functional SBEs within the proximal promoter of the human SnoN gene, which were found to be conserved in the mouse (64). It is curious to note that the Ski gene does not appear to be a direct target of TGF-␤ 1 signaling, which suggests yet another level of complexity to the cellular control of the members of the Ski family of negative TGF-␤ 1 regulators.…”
supporting
confidence: 77%
“…We also found that SOX2 binds the BCL11A locus at multiple sites suggesting a strong direct regulation at the transcriptional level further supporting the data in Figure 3c and d (Figure 3k). BCL11A and SOX2 peaks on SETD8 22,23 , SKIL 24 , TBX2 25 and BCL11A were validated and confirmed by ChIP-qPCR (Supplementary Figure 9). The overlap of the ChIP-Seq peaks suggests a direct interaction between BCL11A and SOX2 proteins, which was confirmed in co-immunoprecipitation experiments on LK2 and H520 (Supplementary Figure 10a, b).…”
Section: Mainmentioning
confidence: 73%
“…Therefore, there is an adequate theoretical basis to investigate the effects of triptolide on AS. Bone morphogenetic proteins (BMPs) are a family of proteins with multiple biological functions, which can specifically bind to and activate receptors on the membrane of target cells, with small mothers against decapentaplegic (Smad) being the classical pathway of BMP signal transduction (6)(7)(8). The molecular basis and mechanism of control of the BMP/Smad pathway has been investigated extensively, and it has been suggested that AS is treated through this pathway.…”
Section: Introductionmentioning
confidence: 99%